The new ambidextrous universe : symmetry and asymmetry from mirror reflections to superstrings - Gardner, Martin, 1914-; Gardner, Martin, 1914- (New York, NY : W.H. Freeman, 1990)
Discusses symmetry and asymmetry in natural laws, and matter and antimatter in the surrounding world and into the universe.
Rev. ed. of: The ambidextrous universe. 2nd rev., updated ed. 1979.
Includes bibliographical references (p. 350-353) and index.
Young Adult
Keywords: Parity nonconservation; Particles (Nuclear physics); Symmetry (Physics); Parity nonconservation; Particles (Nuclear physics); Symmetry (Physics)